2019
DOI: 10.12688/wellcomeopenres.15467.3
|View full text |Cite
|
Sign up to set email alerts
|

Is diabetes associated with malaria and malaria severity? A systematic review of observational studies

Abstract: Background: We conducted a systematic review to study the association between diabetes and malaria as well as malaria severity. Methods: The search was conducted in Embase, Global Health, MEDLINE, Scopus and Web of Science. Titles and abstracts were screened, full-text studied and information extracted for qualitative synthesis. Risk of bias was assessed with ROBINS-I criteria. The exposure was diabetes and the outcome malaria or malaria severity. Results: Of 1992 results, three studies were included (n=7,226)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…HLA-A*24 is reported as "an independent predictor of 5-year progression to diabetes in autoantibody-positive first-degree relatives" of patients with Type I diabetes ( Mbunwe et al., 2013 ). Malaria is also associated with diabetes ( Danquah et al., 2010 ; Acquah, 2019 ; Carrillo-Larco et al., 2019 ). In the mentioned COVID-19 study ( Warren and Birol, 2020 ), HLA class II alleles DPA1*02:02 and DPB1*05:01 were found to be frequent as well.…”
Section: Discussionmentioning
confidence: 99%
“…HLA-A*24 is reported as "an independent predictor of 5-year progression to diabetes in autoantibody-positive first-degree relatives" of patients with Type I diabetes ( Mbunwe et al., 2013 ). Malaria is also associated with diabetes ( Danquah et al., 2010 ; Acquah, 2019 ; Carrillo-Larco et al., 2019 ). In the mentioned COVID-19 study ( Warren and Birol, 2020 ), HLA class II alleles DPA1*02:02 and DPB1*05:01 were found to be frequent as well.…”
Section: Discussionmentioning
confidence: 99%
“…Talking about resistant infections in the field of non-communicable diseases is new, yet some authors have already highlighted the links between communicable and non-communicable diseases. [5][6][7][8] A surveillance system of antibiotic resistance profiles among people with T2DM could be implemented to identify the most dangerous bacteria, select the best treatment considering other concomitant risk factor such as obesity, 86 and monitor trends of the resistance patterns in the T2DM community. An antibiotic resistance surveillance programme could inform local and international guidelines for infections in people with T2DM.…”
Section: Public Health and Clinical Practice Implicationsmentioning
confidence: 99%
“…[1][2][3][4] While much of the research about T2DM has focused on its determinants, consequences and complications regarding non-communicable diseases, T2DM as a risk and prognostic factor for infectiouscommunicable-diseases has gained attention lately. [5][6][7][8] In this relatively novel field-T2DM and infectious diseases-antibiotic resistance remains understudied, though it carries a large disease burden globally and in LMICs. [9][10][11][12][13] Large studies about T2DM and antibiotic resistance have focused on one pathogen or colonisation (rather than infection).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The prevention and control of NCDs should share equal importance with communicable diseases [ 15 ]. Prior studies have indicated that NCDs may be associated with malaria and malaria severity [ 16 18 ]. In several studies from Africa, malaria has been documented to be more common in people with diabetes [ 19 ].…”
Section: Introductionmentioning
confidence: 99%